Anterior Shoulder Instability: The Role of Advanced Shoulder Imaging in Preoperative Planning - Larribe, Maud; Laurent, Pierre-Eloi; Acid, Souad; Aswad, Richard; Champsaur, Pierre; Le Corroller, Thomas (Seminars in Musculoskeletal Radiology, 2014)
Despite advances in the understanding of anterior shoulder instability, recurrence rates after arthroscopic and open surgery have been reported to be as high as 30%. A successful operative outcome for patients with anterior shoulder instability requires the surgeon to perform a complete preoperative evaluation based on a thorough physical examination and advanced imaging techniques. In addition to the Bankart lesion, the treating surgeon must be aware of other copathologies, such as bony lesions of the glenoid or humeral head, humeral avulsion of the glenohumeral ligament, and articular cartilage defects that can occur in concert with capsular pathology and may necessitate a change in surgical strategy. This article focuses specifically on the osseous, labroligamentous, cartilage, and rotator cuff lesions demonstrated on preoperative imaging that are important to recognize in the preoperative work-up to optimize surgical outcomes for anterior instability.
Keywords: shoulder; instability; arthrography; computed tomography; MR imaging